Convergent evolution of health information management and health informatics - Gibson, C. J.; Dixon, B.E.; Abrams, K. (Applied Clinical Informatics, 2015)
Clearly defined boundaries are disappearing among the activities, sources, and uses of health care data and information managed by health information management (HIM) and health informatics (HI) professionals. Definitions of the professional domains and scopes of practice for HIM and HI are converging with the proliferation of information and communication technologies in health care settings. Convergence is changing both the roles that HIM and HI professionals serve in their organizations as well as the competencies necessary for training future professionals. Many of these changes suggest a blurring of roles and responsibilities with increasingly overlapping curricula, job descriptions, and research agendas. Blurred lines in a highly competitive market create confusion for students and employers.In this essay, we provide some perspective on the changing landscape and suggest a course for the future. First we review the evolving definitions of HIM and HI. We next compare the current domains and competencies, review the characteristics as well as the education and credentialing of both disciplines, and examine areas of convergence. Given the current state, we suggest a path forward to strengthen the contributions HIM and HI professionals and educators make to the evolving health care environment.Citation: Gibson CJ, Dixon BE, Abrams K. Convergent evolution of health information management and health informatics – a perspective on the future of information professionals in health care. Appl Clin Inf 2015; 6: 163–184http://dx.doi.org/10.4338/ACI-2014-09-RA-0077
Keywords: Information management; informatics; competency-based education